Case Report: Hypoglycemia Due to Metastatic Insulinoma in Insulin-Dependent Type 2 Diabetes Successfully Treated With 177 Lu-DOTATATE - Kumar, Shejil; Melek, Mariah; Rohl, Peter (Frontiers in Endocrinology, 2022)
We describe a 96-year-old man with insulin-dependent type 2 diabetes mellitus who, despite insulin cessation, presented with recurrent hypoglycemia associated with confirmed inappropriate endogenous hyperinsulinemia. 68Ga-DOTATATE-PET/CT scans demonstrated increased uptake in the pancreatic tail with multiple large intensely active liver metastases. Liver biopsy confirmed the diagnosis of well-differentiated metastatic neuroendocrine tumor. He was unsuitable for surgical resection and long-acting somatostatin analogue therapy was ineffective. Subsequent management with four cycles of Lutate (177-Lutetium-DOTA0-Tyr3-octreotate (177Lu-DOTATATE)) resulted in resolution of hypoglycemia, and ongoing clinical, biochemical and radiological response six years after. This case is unique not only due to the paradoxical entity of insulinoma in insulin-dependent diabetes but also the positive sustained outcome after Lutate, given unresectable metastatic insulinoma carries a poor prognosis. We review published cases of metastatic insulinoma in patients with diabetes mellitus as well as the literature to-date investigating efficacy and safety of Lutate therapy in metastatic insulinoma.